Residential exposure to transportation noise and risk of incident atrial fibrillation: a pooled study of 11 prospective Nordic cohortsResearch in context - Jesse D. Thacher; Nina Roswall; Mikael Ögren; Andrei Pyko; Agneta Åkesson; Anna Oudin; Annika Rosengren; Aslak H. Poulsen; Charlotta Eriksson; David Segersson; Debora Rizzuto; Emilie Helte; et al. (Elsevier, 2024)
Summary: Background: Transportation noise has been linked with cardiometabolic outcomes, yet whether it is a risk factor for atrial fibrillation (AF) remains inconclusive. We aimed to assess whether transportation noise was associated with AF in a large, pooled Nordic cohort. Methods: We pooled data from 11 Nordic cohorts, totaling 161,115 participants. Based on address history from five years before baseline until end of follow-up, road, railway, and aircraft noise was estimated at a residential level. Incident AF was ascertained via linkage to nationwide patient registries. Cox proportional hazards models were utilized to estimate associations between running 5-year time-weighted mean transportation noise (Lden) and AF after adjusting for sociodemographics, lifestyle, and air pollution. Findings: We identified 18,939 incident AF cases over a median follow-up of 19.6 years. Road traffic noise was associated with AF, with a hazard ratio (HR) and 95% confidence interval (CI) of 1.02 (1.00-1.04) per 10-dB of 5-year mean time-weighted exposure, which changed to 1.03 (1.01-1.06) when implementing a 53-dB cut-off. In effect modification analyses, the association for road traffic noise and AF appeared strongest in women and overweight and obese participants. Compared to exposures ≤40 dB, aircraft noise of 40.1-50 and > 50 dB were associated with HRs of 1.04 (0.93-1.16) and 1.12 (0.98-1.27), respectively. Railway noise was not associated with AF. We found a HR of 1.19 (1.02-1.40) among people exposed to noise from road (≥45 dB), railway (>40 dB), and aircraft (>40 dB) combined. Interpretation: Road traffic noise, and possibly aircraft noise, may be associated with elevated risk of AF. Funding: NordForsk.